Pengembangan Aplikasi Panduan Pengenalan Kampus Universitas Siliwangi Berbasis Augmented Reality Pada Perangkat Android - Rhoza Prasetia; Eka Wahyu Hidayat; Rahmi Nur Shofa (Maranatha University Press, 2018)
Siliwangi University annually holds a new student registration. Before entering the lecture activities, students are required to follow the student orientation program. However, the quality of given material, provided time, with physical and psychological condition of the students during the orientation become a barrier in the absorption of campus introduction information. Knowledge of campus building, the faculty which includes faculty staff, and available facilities will become the student needs in the course of support every campus activity. Based on that identified problems, application of augmented reality-based introduction guide on Android device become a solution in campus introduction of Siliwangi University to users, both for the academic community. The concept of this application is to introduce the campus buildings through an installed camera on the user's smartphone. By pointing smartphone camera to a monumental looking facility or building, users will get information about the building's description, lecturers and staff list, and photo gallery. The application which developed using the Luther-Sutopo method has been tested by alpha testing which results are functionally appropriate, as well as on beta testing obtaining a value of 70.6% of the constructed application is declared feasible to be used with the